The dynamic shear properties of magnetorheological elastomers modeled by the Kelvin-Voigt model - de Carvalho, Henrique Edno Leoncini; Fukushima, Jeferson Camargo [UNESP]; Obata, Daniel Henrique de Sousa [UNESP]; Proença, Matheus Silva [UNESP]; de Almeida, Fernanda Carolina [UNESP]; Paschoalini, Amarildo Tabone [UNESP] (FapUNIFESP (SciELO), 2024)
Magneto Rheological Elastomers (MRE) are composite intelligent materials, which can substantially change their viscoelastic properties due to their high magneto-sensitivity in response to different regimes of external magnetic field. The practical application of MR materials demonstrates great potential for several areas, as indicates the increasing number of patents registered in the last decade. For the dynamic characterization of the material, an original experimental arrangement was developed, from the creation of customized algorithms to the physical assembly of equipment, with the setup consisting of basic equipment used in vibration studies. Tests were carried out with a maximum strain of below 2.5%, the sampling frequency varied between 10 – 60 Hz under a single manually controlled input stress, with average between cycles of 1.66 kPa, and 2.19% deviation. The results showed expected behaviour and coherence with similar research, showing a gain in viscoelastic properties of 239% for shear modulus and 466% for viscosity in the maximum field of 500 mT. The Kelvin-Voigt model was used to numerically obtain the material properties, the error linked to the model (adaptation) was quantified at each acquisition cycle, with an average value of 6.33%, considered satisfactory by the work group, since the application in structures requires safety coefficients with higher values. The results obtained deepen the understanding of the material’s behaviour, exploring specific input values, and also demonstrate the viability of the experimental setup and the application of MREs for the development of vibration control devices.
Keywords: Characterization; Elastomer; Intelligent materials; Kelvin-Voigt; Magnetorheological